SIFAT FISIKOKIMIA MINYAK KAYU PUTIH JENIS Asteromyrtus brasii - Ary Widiyanto; Mohamad Siarudin (Jurnal Penelitian Hasil Hutan, 2014)
Asteromyrtus brassi, is one of the cajuput oil tree species in Wasur National Park, Merauke, Papua. However, the information on the chemical compound and physical properties (qualities) of cajuput oil produced from this species is still limited. This research aimed to measure the chemical compound and physical properties of cajuput oil distilled from the leaves of A.brassi trees which grow at the Wasur National Park. Chemical compound analysis is using Gas Chromatography and Mass Spectrometer method (GC-MS method). The analysis on the physical properties was applied to the cajuput oil distilled using steam method. The distillation lasted for 4-5 hours, and every interval of 30 minutes the distilled cajuput oil collected cumulatively and the total collected oil was examined for the yield and physco-chemical properties. The qualities of the overall cajuput oil from A. brassi- tree leaves couldn’t satisfy the standard (SNI 06-3954-2006) because of the specific gravity is below 0.9 and optical rotation of 9.8. Analysis result with GC-MS show there are 29 peak, with 5 of them has the higher intensity identified as 1,8 cineole (34,88% concentration), Trans-Beta-Ionon-5,6-Epoxide (21,26%), Formamide (CAS) Methanamide (11,20%), Acetic acid (CAS) Ethylic acid (8,14%) and Alpha pinene (4,39%).